Immersion, médias sociaux et récit transmédiatique - Philippe Gauthier (Communication)
The author aims to more directly investigate the integration of social media into transmedia storytelling through the creation of “official” accounts for fictional characters. He has two objectives. First, he analyzes a specific case to show how the presence of fictional characters on social media creates new relationships between the fictional world and the interactor’s reality. Then he attempts to determine how these new relationships undermine the concepts of immersion and the magic circle.